Automatic oral fluid‐based HIV testing in HIV screening programmes: automatic for the people. (28th August 2013) - Rayment, M; Doku, E; Thornton, A; Pearn, M; Sudhanva, M; Jones, R; Nardone, A; Roberts, P; Tenant‐Flowers, M; Anderson, J; Sullivan, AK; Atkins, M
Abstract : Objectives: UK guidelines recommend routine HIV testing in general clinical settings when the local HIV prevalence is > 0.2%. During pilot programmes evaluating the guidelines, we used laboratory‐based testing of oral fluid from patients accepting tests. Samples ( n = 3721) were tested manually using the Bio‐Rad Genscreen Ultra HIV Ag‐Ab test (Bio‐Rad Laboratories Ltd, Hemel Hempstead, UK). This was a methodologically robust method, but handling of samples was labour intensive. We performed a validation study to ascertain whether automation of oral fluid HIV testing using the fourth‐generation HIV test on the Abbott Architect (Abbott Diagnostics, Maidenhead, UK) platform was possible. Methods: Oral fluid was collected from 143 patients (56 known HIV‐positive volunteers and 87 others having contemporaneous HIV serological tests) using the Oracol+ device (Malvern Medicals, Worcester, UK). Samples were tested concurrently: manually using the Genscreen Ultra test and automatically on the Abbott Architect. Results: For oral fluid, the level of agreement of results between the platforms was 100%. All results agreed with HIV serology. The use of the Oracol+ device produced high‐quality samples. Subsequent field use of the test has shown a specificity of 99.97% after nearly 3000 tests. Conclusions: Laboratory‐based HIV testing of oral fluid requires less training of local staff, with fewer demands on clinical time and space than near‐patient testing. It is acceptable to patients. The validation exercise and subsequent clinical experience support automation, with test performance preserved. Automation reduces laboratory workload and speeds up the release of results. Automated oral fluid testing is thus a viable option for large‐scale HIV screening programmes.